An evaluation of identity and access management systems. (26th January 2021) - Sanjalawe, Yousef K.; Anbar, Mohammed; Al-zoubi, Qusay M.
One of the most critical issues of all of networks types that integrate the both of wired and wireless technologies is the performance and applicability of the electronic authentication and identification techniques. These schemes involve various technologies of different levels of security. This research presents a comparative study of six IDAM available tools, based on the three characteristics (ease of use, usefulness, and user's satisfaction), which build targets to be achieved in order to gain quality in software. The tools compared in this study are Log Mote, Oracle ID management, Tivoli Identity Manager, NetIQ-Novell, Access Sentinel, and Active Directory. In order to enable users to access the available resources in a secure way, we propose a novel architecture of IDAM. The proposed architecture basically has several advantages like, autonomy, comprehensive and systematic, standardization, and scalability.